Diversidade e Tolerância de Fungos Endolíticos em Plantas Sujeitas a Estresses Causados por Metais Pesados - SILVA, Leandro Souza (2018)
One of the main problems of the contemporary world is the contamination of soil and water by heavy metals. Many microorganisms, such as fungi, for example, may interact with these heavy metals in the environment acquiring the ability to survive by adaptation or mutations, and are considered promising bioremediation agents. The objectives of this study were: (I) to evaluate the frequency of endophytic fungi in plants of sites subject to contamination by heavy metals, and (II) to evaluate the in vitro tolerance of these fungi to mercury. Leaves of eight plant species were collected along the river banks of the Sabino Tributary Stream, in a region heavily influenced by the Sanitary Landfill of Ribeira, São Luís, Brazil. These leaves were surface disinfested and plated in BDA medium. The recovered endophytic fungi were purified, identified and deposited in the mycological collection of NIBA / UFMA. The mercury tolerance of the 10 predominant species was evaluated by the mycelial growth of these in plates with BDA medium supplemented with HgCl2 in seven concentrations (1 to 7 mg.mL-1). In total, 54 isolates were obtained. Fungi belonged to 28 morphological types distributed in 11 genera. The Tolerance Index (TI) and Mycelial Growth Rate Index analyzes indicated that, despite differences in behavior under stress caused by mercury, many fungi exhibited satisfactory levels of tolerance to the metal. Scytalidium lignicola and Trichoderma sp. showed high tolerance and high growth in media containing high concentrations of HgCl2, indicating the possibility of the use of these fungi in bioremediation essays of contaminated environments.